Successful Management of Thyroid Storm with Continuous Renal Replacement Therapy without Plasma Exchange - Calvin Kurnia Mulyadi; Elizabeth Yasmine Wardoyo; Anggraini Permata Sari; Aryan Yohanes; Johanes Sarwono; Fidkya Allisha; Marina Epriliawati; Muhammad Ikhsan Mokoagow (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Thyroid storm is a life-threatening endocrine emergency that needs urgent management. Conventional therapies, however, may not always yield satisfactory outcome. Hereby, we report a case of refractory thyroid storm with hemodynamic and cardiac instability that showed significant improvement following continuous renal replacement therapy (CRRT) instead of therapeutic apheresis. Case Illustration: A 46-year-old woman presented to the emergency department with severe thyrotoxicosis and pneumonia. On arrival, she was alert and hemodynamically stable. Physical examination revealed rapid irregular heart rate, fever, exophthalmos, diffuse goitre, and bilateral pulmonary rales. Laboratory findings indicated primary thyrotoxicosis, remarkable leukocytosis, and high procalcitonin that was consistent with sepsis. The Burch-Wartofsky score was 65, indicating thyroid storm. Clinical deterioration including loss of consciousness occurred on the next few days with electrocardiography changing into unstable supraventricular tachycardia despite optimal medical treatment administered to manage thyrotoxicosis and infection. Due to a suboptimal response, continuous veno-venous hemofiltration (CVVH) was initiated for 33 hours. This resulted in marked clinical improvement, including a reduction in free thyroxine (fT4), hemodynamic stabilization and recovery of consciousness. Discussion: While therapeutic plasma exchange (TPE) is the recommended adjunctive therapy for refractory thyroid storm according to the ASFA 2016 guidelines, it is often unavailable in many centers, particularly in low-resource settings. CRRT may serve as an alternative, offering hemodynamic stabilization through mechanisms not yet fully understood. Conclusion: CRRT may be considered a safe and effective alternative treatment for thyroid storm in patients who are refractory to standard medical therapy and particularly for those presenting with hemodynamic instability.